Sensitivity of Nasal Bone as Aneuploidy Marker—First Trimester versus Second Trimester Assessment - Lakshmy, Selvaraj Ravi; Shobana, Umapathy; Rose, Nity (Journal of Fetal Medicine, 2017)
Objective To assess the reliability of nasal bone (NB) as an aneuploidy marker in the first trimester vs. second trimester and to highlight the technical difficulties in evaluating the nasal bone at 11–14 week scan.Methods Nasal bone was examined in 4478 women who enrolled for nuchal translucency (NT) scan and NB was assessed in both midsagittal and coronal planes. Risk assessment was done based on serum biochemistry and NT without including the NB status. Absence of NB was confirmed at 17 week and aneuploidy risk was modified from the obtained first trimester risk. The midsagittal images from the cases with absent NB were randomly assorted among 81 normal ones and were peer reviewed.Results Nineteen fetuses had absent NB in the first trimester, of which five had NT above the 90th percentile. In the remaining 14 cases followed up at second trimester, nasal bone was present in 3 cases in the subsequent scan. Five of 11 cases were screen positive after modifying the risk and were counseled appropriately. In retrospective evaluation of the 100 images, concordance was obtained only in 76%, reflecting the observer variability. Down’s syndrome was confirmed in 4 cases of which three also had an increased NT.Conclusions Routine inclusion of NB in first trimester risk assessment with conventional midsagittal view alone in all cases may lead to an increased number of false positives. Inclusion in the second trimester would still have the same detection rate but would eliminate technical difficulties of imaging NB in the first trimester.
Keywords: Nasal bone; Aneuploidy; Retronasal triangle; Midsagittal plane; Equal sign; First trimester screening; Nuchal translucency; Non-invasive prenatal testing